A mechanistic modelling methodology for microstructure-sensitive fatigue crack growth - Wilson,D; Dunne,FPE (Journal of the Mechanics and Physics of Solids, 2019)
A mechanistic methodology for simulating microstructurally-sensitive (tortuosity and propagation rate) fatigue crack growth in ductile metals is introduced which utilises the recently introduced dislocation configurational stored energy as the measure of the driving force. The model implements crystal plasticity finite element simulations using the eXtended Finite Element Method (XFEM) to represent the crack. Two methods of predicting the direction of growth (based on the crystallographic slip or the maximum principal stress) are compared. The crystallographic slip based direction model is shown to predict microstructurally-sensitive fatigue crack growth in single crystals which displays many features of path tortuosity that have been observed experimentally. By introducing a grain boundary, the crystallographic model is shown to capture behaviour similar to that observed experimentally including crack deflection and retardation at the grain boundaries. Finally, two experimental examples of fatigue cracks growing across three grains are analysed, and the model is shown to capture the correct crystallographic growth paths in both cases.